Anti-diabetic Effects of Clostridium butyricum CGMCC0313.1 through Promoting the Growth of Gut Butyrate-producing Bacteria in Type 2 Diabetic Mice - Lingling Jia (Nature Portfolio, 2017)
Abstract Patients with type 2 diabetes (T2D) have decreased butyrate-producing bacteria. We hypothesized that supplementation with butyrate-producing bacteria may exert beneficial effects on T2D. The current study investigated the effects of well-characterized butyrate-producing bacteria Clostridium butyricum CGMCC0313.1 (CB0313.1) on hyperglycemia and associated metabolic dysfunction in two diabetic mouse models. CB0313.1 was administered daily by oral gavage to leptin db/db mice for 5 weeks starting from 3 weeks of age, and to HF diabetic mice induced by high fat diet (HFD) plus streptozotocin (STZ) in C57BL/6J mice for 13 weeks starting from 4 weeks of age. CB0313.1 improved diabetic markers (fasting glucose, glucose tolerance, insulin tolerance, GLP-1 and insulin secretion), and decreased blood lipids and inflammatory tone. Furthermore, CB0313.1 reversed hypohepatias and reduced glucose output. We also found that CB0313.1 modulated gut microbiota composition, characterized by a decreased ratio of Firmicutes to Bacteroidetes, reduced Allobaculum bacteria that were abundant in HF diabetic mice and increased butyrate-producing bacteria. Changes in gut microbiota following CB0313.1 treatment were associated with enhanced peroxisome proliferator–activated receptor-γ (PPARγ), insulin signaling molecules and mitochondrial function markers. Together, our study suggests that CB0313.1 may act as a beneficial probiotic for the prevention and treatment of hyperglycemia and associated metabolic dysfunction.